2017
DOI: 10.5194/acp-17-14821-2017
|View full text |Cite
|
Sign up to set email alerts
|

Open burning of rice, corn and wheat straws: primary emissions, photochemical aging, and secondary organic aerosol formation

Abstract: Abstract. Agricultural residues are among the most abundant biomass burned globally, especially in China. However, there is little information on primary emissions and photochemical evolution of agricultural residue burning. In this study, indoor chamber experiments were conducted to investigate primary emissions from open burning of rice, corn and wheat straws and their photochemical aging as well. Emission factors of NO x , NH 3 , SO 2 , 67 non-methane hydrocarbons (NMHCs), particulate matter (PM), organic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 131 publications
5
44
0
Order By: Relevance
“…To convert between organic carbon and organic matter (OM), a default OM/OC mass ratio of 1.6 is used in the absence of specific information. This value is based on the data from fresh biomass smoke aerosol in the literature (Turpin and Lim, 2001;Aiken et al, 2008;Yokelson et al, 2009;Takahama et al, 2011;Kostenidou et al, 2013;Brito et al, 2014;Collier et al, 2016;Fang et al, 2017;Tkacik et al, 2017;Ahern et al, 2019;Lim et al, 2019). Where only O/C ratios were given, they were converted to OM/OC ratios using the relationship given in Aiken et al (2008).…”
Section: Data Selectionmentioning
confidence: 99%
“…To convert between organic carbon and organic matter (OM), a default OM/OC mass ratio of 1.6 is used in the absence of specific information. This value is based on the data from fresh biomass smoke aerosol in the literature (Turpin and Lim, 2001;Aiken et al, 2008;Yokelson et al, 2009;Takahama et al, 2011;Kostenidou et al, 2013;Brito et al, 2014;Collier et al, 2016;Fang et al, 2017;Tkacik et al, 2017;Ahern et al, 2019;Lim et al, 2019). Where only O/C ratios were given, they were converted to OM/OC ratios using the relationship given in Aiken et al (2008).…”
Section: Data Selectionmentioning
confidence: 99%
“…In this equation, E* i,j (kg/kg) is the emission factor and it describes the amount of pollutant i typically emitted per unit mass of crop j. Multiple studies have been conducted to determine the emission factors associated with agricultural burning under controlled conditions [1] and by field measurements [23]. Table 1 shows E* i,j and L j for several crops.…”
Section: Estimation Of the Pollutants' Mass Emission Ratesmentioning
confidence: 99%
“…They represent the opinion of the scientific community that exposure at or below the level of the TLV does not create an unreasonable risk of disease or injury [3]. Aiming to provide public health protection, including protecting the health of "sensitive" populations such as asthmatics, children, and the elderly, the environmental authority specifies those threshold limit values in the NAAQS for short time periods of exposure (3, 8, or 24 h depending of the pollutant) and for long time periods of exposure (one year) [14][15][16][17][18][19][20][21][22][23][24]. In this work, we only consider short-term exposition, as agricultural burnings are short-term events.…”
Section: Determination Of the Influence Areamentioning
confidence: 99%
“…As a result, a new capture vaporizer (CV) with an enclosed cavity was developed (Xu et al, 2017b). Field measurements showed that the CE of CV-AMS was fairly robust at ~1 (Hu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%